The forgotten beasts of Eld - McKillip, Patricia A. (Gollancz, 2015)
Sybel, the beautiful great-granddaughter of the wizard Heald, has grown up on Eld Mountain with only the fantastic beasts summoned there by wizardry as companions. She cares nothing for humans until, when she is 16, a baby is brought for her to raise, a baby who awakens emotions that she has never known before. But the baby is Tamlorn, the only son of King Drede, and, inevitably, Sybel becomes entangled in the human world of love, war and revenge - and only her beasts can save her from the ultimate destruction...